Development of Android-Based Educational Application "ASTUTIK-APP" as Stunting Screening Media in North Sumatra - Susilawati, Susilawati; Darmayanti, Nefi; Angeli, Bintang Rizki; Andayani, Lita Sri (Indonesian Journal of Global Health Research, 2024)
Stunting is a serious nutritional problem that is still high in Indonesia, including in North Sumatra Province. Based on SSGI data (2022), the prevalence of stunting in Indonesia reached 21.6%. The government targets a reduction in this prevalence to 14% by 2024, with an annual decrease of 3.8%. However, in North Sumatra, despite a decrease from 25.8% in 2021 to 21.1% in 2022, several areas such as Langkat (39.4%), Samosir (30.8%), and Tanjung Balai City (26.9%) still have a high prevalence of stunting. Objective: "ASTUTIK-APP" aims to provide information and education to parents about stunting in a complete, accurate and reliable manner. Not only complete, the ASTUTIK application also carries an up-to-date concept so that all users can find out the latest information related to stunting such as educational videos related to stunting. Results: The results of the feasibility study of the "ASTUTIK" APP Application from the completeness of features, Effectiveness and Accessibility are very high compared to the existing Stunting Application. Conclusions: The results of the feasibility study of the "ASTUTIK" APP Application from the completeness of features, Effectiveness and Accessibility are very high compared to the existing Stunting Application.